Sol–gel synthesis and characterization of Li2CO3–Al2O3 composite solid electrolytes - Sulaiman, M.; Rahman, A.A.; Mohamed, N.S. (Springer Verlag (Germany), 2016)
Composite solid electrolytes in the system (1−x-)Li2CO3-xAl2O3, with x=0.0-0.5 (mole), were synthesized by a sol-gel method. The synthesis carried out at low temper- ature resulted in voluminous and fluffy products. The obtained materials were characterized by X-ray diffraction, differential scanning calorimetry, scanning electron microscopy/energy- dispersive X-ray, Fourier transform infrared spectroscopy and AC impedance spectroscopy. Structural analysis of the samples showed an amorphous feature of Li2CO3 and traces of α-LiAlO2, γ-LiAlO2 and LiAl5O8. The prepared composite samples possess high ionic conductivities at 130-180 °C on account of the presence of lithium aluminates as well as the formation of a high concentration of an amorphous phase of Li2CO3 via this sol-gel preparative technique.